PENGARUH CSR TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA PERIODE 2018 - 2022 - Rampengan, Edgar Franz Bartholomew; Suaryana, I Gusti Ngurah Agung; Joy, Joy (Jurnal Ilmiah Wahana Pendidikan, 2024)
Corporate Social Responsibility is something very important because Corporate Social Responsibility is one of the company's ways to get a good image in the eyes of many people. The purpose of this study is to determine the effect of disclosure Corporate Social Responsibility on profitability in banking companies on the Indonesia Stock Exchange (IDX). The grand theory used in this research is signal theory, legitimacy theory and stakeholder theory. The profitability variable is proxied by Return on Assets. This research was conducted on companies listed on the Indonesia Stock Exchange (IDX) in 2018 – 2022. The population for this study was 43 companies with 5 years of observation, which was then determined by using the purposive sampling technique. Samples used in this study is 31 companies. Data from this study is collected using observation non participant technique. The Data analysis technique used in this study is simple linear regression analysis. The results of this study indicate that the disclosure of Corporate Social Responsibility does not affect the profitability of the companies.